Devenir autonome, encore et en corps, au prisme des œuvres de formation - Camille Roelens (Mise au Point)
This text proposes a philosophical reflection on what, in the contemporary process of forming oneself as an autonomous subject, affects the relationship to one's own body. This staging of an individual's body as an essential vector of his or her autonomous becoming seems to us to be expressed in an exemplary way in the cinematic work La vie d'Adèle (2013) - Kechiche's free adaptation of Maroh's graphic novel Le bleu est une couleur chaude (2010). We first show that the analytical framework of the formative novel, or Bildungroman, can be applied - skilfully subverted - with strong heuristic interest to these two works (1), and then present the challenges of self-formation for the contemporary individual that are the subjective appropriation of the body and learning to chairir oneself (2). We then focus on the character of Adèle in the cinema, as a counterpoint to Clémentine's between bubbles and boxes, which inspired it, and show how Adèle (the character) and Adèle Exarchopoulos (her interpreter) embody, in the strongest sense, the hypermodern individual becoming (3). Finally, we suggest the importance, for present-day thinking on self-formation, of the multiplication of publications of works of formation fully inscribed in their hypermodern time and the democratization of access to the most varied cultural contents (4).